Plasma Free Choline Concentration Did Not Reflect Dietary Choline Intake in Early and Late Pregnancy: Findings from the APrON Study. (29th May 2020) - Mujica, Maria; Lewis, Erin; Jacobs, Rene; Letourneau, Nicole; Bell, Rhonda; Field, Catherine; Lamers, Yvonne
Abstract: Objectives: Choline is a critical nutrient for fetal development. Pregnancy studies showed that most women have choline intakes below the adequate intake (AI) level of 450 mg/d. Research on plasma free choline as an indicator of dietary choline intake showed conflicting results to date. We sought to compare plasma free choline concentration between women with different choline intakes and to explore the association between plasma free choline and dietary choline intake in early (EP) and late pregnancy (LP). Methods: This study included data and non-fasting plasma samples from pregnant women enrolled in the Alberta Pregnancy Outcomes and Nutrition (APrON) cohort study. EP (<20 weeks of gestation) and LP (>20 weeks of gestation) dietary choline intake was estimated using a 24-hr recall. Two categories of dietary choline intake were created: 1) low choline (LCI), i.e., choline intake in 1st quartile (Q) in EP, with these women having choline intake in 1st or 2nd Q in LP (n = 61); 2) high choline intake (HCI), i.e., choline intake in 4th Q in EP and in 3rd or 4th Q in LP (n = 46). Linear mixed-effects models were used to explore the association between plasma free choline and dietary choline intake across EP and LP, after adjustment for maternal age, ethnicity and weeks of gestation. Results: Median (IQR) maternal age was 32 (30–35) y, and 80% were Caucasian. LCI was 101 (86–109) and 109 (93–127) mg/day in EP and LP, respectively, and HCI was 251 (223–286) and 212 (177–274) mg/day. Plasma free choline (μmol/L) did not differ between LCI and HCI at E P  [LCI: 10.6 (9.03, 12.9); HCI: 11.7 (10.2, 13.8)] and L P  [LCI: 11.7 (10.6, 12.7); HCI: 12.7 (10.7, 15.8)] ( P  > 0.05, Wilcoxon rank-sum test). Per 10 mg of choline intake, plasma free choline increased by 0.34 (95%CI 0.12, 0.56) in those with LCI, and 0.18 (95%CI 0.050, 0.31) in women with HCI, across EP and LP after adjustment. Conclusions: In this subgroup of pregnant women, plasma free choline concentration did not reflect differences in dietary choline intake in EP or LP. This may be explained by an overall low choline intake (<AI) which would promote rapid tissue uptake of choline. The identification of a sensitive and dynamic biomarker for choline status is required. Funding Sources: UBC Four Year Doctoral Fellowship, Canada Research Chair Program, CIHR NTE Grant FRN 160, 942, Alberta Innovates for the APrON cohort.